Professional Football Club Management Analysis in Indonesia Case Study on Bali United Fc - Wijaya, John Henry; Saputera, Denny; Hertina, Dede (SAFE-Network, 2023)
Along with the development of professional football in Indonesia, professional football clubs increasingly need good and correct financial management. One important indicator in professional football club financial management is financial ratios. Bali United FC has a large and successful fan base in recent years. Bali United FC is one of the most famous professional football clubs in Indonesia. However, in its management there are several problems that need to be overcome so that the club can continue to grow and compete with other clubs. Apart from that, there are also problems with the development of the club's business and a lack of support from the government and sponsorship. The purpose of this research is to identify the types of financial ratios used in the financial management of professional football clubs in Indonesia. Describe the financial performance of Bali United FC based on the financial ratios used. Identify the factors that influence the management of financial ratios at Bali United FC. This research uses a case study approach with the object of research Bali United FC.